Evaluating search and matching models using experimental data - Jeremy Lise; Shannon Seitz; Jeffrey Smith (IZA Journal of Labor Economics, 2015)
This paper introduces an innovative test of search and matching models using the exogenous variation available in experimental data. We take an off-the-shelf search model and calibrate it to data on the control group from a randomized social experiment. We then simulate a program group from a randomized experiment within the model. As a measure of the performance of the model, we compare the outcomes of the program groups from the model and from the randomized experiment. We illustrate our methodology using the Canadian Self-Sufficiency Project (SSP), a social experiment providing a time-limited earnings supplement for Income Assistance recipients who obtain full-time employment within a 12-month period. We find two features of the model are consistent with the experimental results: endogenous search intensity and exogenous job destruction. We find mixed evidence in support of the assumption of fixed hours of labor supply. Finally, we find a constant job destruction rate is not consistent with the experimental data in this context.
Keywords: J2; I38; J6; 330; Policy experiments; Search and matching; Self-sufficiency project; Social experiments